Pemberdayaan Perempuan melalui Bank Sampah Anugrah untuk Menambah Penghasilan Keluarga di Kelurahan Siwalan Kota Semarang - Oktavianingtyas, Esa Rizqy; Desmawati, Liliek; Loretha, All Fine (Peneliti.net, 2024)
This study aims to describe women's empowerment through the anugrah waste bank and describe the supporting and inhibiting factors. This study uses a descriptive qualitative research method. Collecting data using observation techniques, interviews, and documentation. The research subjects consisted of the chairman, 2 administrators, and two customers. The results of the study show that efforts to empower women in providing additional income are through waste savings owned by customers and additional knowledge. Women already have the awareness to take part in waste bank activities and the importance of a woman being empowered. Women's participation is as a customer and administrator of a gift waste bank. The level of control cannot be maximized because it is still limited and uneven. The supporting factors are the availability of adequate resources and the support from the government and BNI 46. The inhibiting factors are the unavailability of a special building for waste bank activities. The conclusion is that women's empowerment has been running, even though it is not optimal, but it has been able to help customers increase their income. Suggestions from researchers are to hold training again and be more active in conducting outreach.